Nitrogen Enhancement of Phosphate Transport in Roots of Zea mays L. : I. Effects of Ammonium and Nitrate Pretreatment - Smith, Frank W. (1987)
The effect of nitrogen status on phosphorous uptake and translocation was examined in 6-day-old dark-grown decapitated maize seedlings exposed to 25 micromolar phosphorous. Transfer to complete solutions containing 1 millimolar ammonium resulted in an increase in phosphorous uptake rate after 6 to 8 hours. The stimulus remained effective for at least 5.5 hours upon subsequent transfer to nitrogen-free solutions. Pretreatments for 16 hours with either nitrate or ammonium resulted in enhanced rates of subsequent phosphorous uptake and in enhanced translocation to the xylem of the exogenously supplied phosphorous. Both processes reached a plateau following pretreatment with 0.1 to 1.0 millimolar concentrations of either nitrogen ion. Further enhancement occurred with 10 millimolar nitrate, but not with 10 millimolar ammonium pretreatment. Although nitrogen pretreatments slightly increased the quantity of exogenous phosphorous retained in the root tissue, most of the extra phosphorous taken up by the nitrogen-pretreated seedlings was translocated to the xylem. The enhanced translocation, however, did not totally account for the increase in uptake implying a specific stimulation of the uptake process.